Directory of European Polar Research funding programmes - Vancauwenberghe, Maaike; Deleu, Philippe; Ørbæk, Jon Børre; Strobel, Anneli; Biebow, Nicole (Zenodo, 2022)
The “Directory of Polar research funding programmes in Europe” is EU-PolarNet 2´s initial step to improve the coordination and cooperation of national polar funding organisations in Europe. The directory provides an overview about the governance, strategies, and procedures of polar research funding in Europe. With publishing this directory, EU-PolarNet 2 aims to contribute to improving the efficiency and effectiveness of European polar research. A better overview and understanding of each other’s activities and structures shall avoid overlap, minimise fragmentation, and ensures the synergetic use of national resources and investments. Please cite as: EU-PolarNet 2 consortium (2022) Directory of European Polar Research funding programmes (Eds. Vancauwenberghe M, Deleu P, Ørbæk JB, Strobel A, Biebow N). 58 pp. Bremerhaven: Alfred Wegener Institute.